A study on use of computers in education among students at UiTM Pahang / Nurain Mohd Yamin, Rafidah Alias and Roshaliza Abdul Rahman - Mohd Yamin, Nurain; Alias, Rafidah; Abdul Rahman, Roshaliza (2011)
The purpose of this study was to investigate a study on use of computers in education among students at UiTM Pahang. The scope of the study was from two programs, which Bachelor of Office System Management and Diploma in Office Management and Technology. In this study, the researchers used stratified proportionate random sampling technique. The technique involved 2-step processes of stratification or segregation, followed by random selection of subjects from each stratum. This descriptive study used survey questionnaires which have been distributed to 100 respondents and the return rate was 100%. Data analyze were done by using PSAW 18.0. This study showed that the majority of the respondents agreed that use of computers can affect the students working with computers in education. From the finding, there were some recommendations that should be taken by both parties which are the potential researchers and the responsible management. Firstly, as recommendation in the future, the researchers should do research that not only focus on one program such as Office Management and Technology but must focus on gender differences in the computer usage from different program such as Computer Science, Accountancy, and others. The management that responsible to the students facilities should improve the Internet facilities all over the place in University in order to facilitate the students to do the assignments and release the students stress. The possible reason and the implications of these findings will be elaborated and discussed.